Begjæret etter bergets dyp og fjellets tinder: Om sider ved det dikteriske fundament hos Ibsen og Hamsun - Arntzen, Even (Nordlit, 2016)
Even though Knut Hamsun stubbornly denied it, all his life he had a strong and ambivalent interest for Henrik Ibsen. Quite well known are Hamsun's many attacks on Ibsen in articles and lectures, letters and novels. Less known is that there are several coinciding (intertextual) motifs between Ibsen and Hamsun. In several of Ibsen's plays and poems the mountain motif is associated with poetic vocation and a descent and entry into an enclosed world of fantasy and imagination. The mountain motif is for sure attached to a form of penetration into a supernatural and demonic underworld, but also related to an upward and vertical movement, towards light, air and literary clarity. One finds strong traces of this double Ibsenian movement also in Hamsun's authorship, for example in the novels Pan and In Wonderland. But Hamsun seems to exceed Ibsen: in Hamsun's literary universe, the mountain motif is also linked to a revitalized dream of happiness, joy and an existential demand of exceeding oneself in the direction of a more authentic way of being human in the modern world.